Forward osmosis for sustainable water treatment - Shen, L; Hankins, N (Elsevier, 2016)
Forward osmosis (FO) as an emerging technology has been researched extensively over the past few decades for water treatment and other applications. In FO, the water in the feed solution (at low osmotic pressure) spontaneously flows through a semipermeable membrane to the draw solution (at high osmotic pressure) under the osmotic pressure difference and without applied hydraulic pressure, conferring the advantages of low energy consumption in the separation process and reduced membrane fouling. For this reason, it is a promising potential candidate for sustainable water processing. Although FO is unlikely to replace reverse osmosis in many applications, it has successfully been employed as a pretreatment process in desalination, wastewater treatment, power generation and life science applications. Some niche applications of stand-alone FO have been identified in food and fertiliser industries, but the majority of practical applications involve FO as a pretreatment process to reduce the energy cost and membrane fouling during subsequent stages of water processing. This chapter will introduce the three key parts in the FO process: the draw solutions, the membranes and the modules, and then discuss the practical applications. The associated challenges in FO are also highlighted within each part, including draw solution development, reverse solute diffusion, concentration polarisation, membrane fouling and FO membrane development. To overcome these challenges, the related developments and modifications are critically discussed with consideration of the overall performance of the FO process.